The effectiveness of communication interdependence between teachers, parents, assessors, and entrepreneurs affecting the work and entrepreneurial skills of vocational high school students - Rosmawaty Hilderiah Pandjaitan; Elena Shinta Maharani Hutajulu (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
This research aims to describe the model, quantity percentage, and factors that affect the effectiveness of communication interdependence between teachers, parents, accessors, and entrepreneurs, affecting vocational high school students' work and entrepreneurial skills (SMKN 7 Tangerang Regency in Industrial Era 4.0). The data analysis method used in this study is used criterion-related validity test in the form of predictive validity, using product-moment correlation technique. This study is quantitative research with a survey method involving 372 respondents from SMKN 7 Tangerang. This study employed Mixing Theory System (Bertalanffy), Theory Open System (Shawn Fanning), and Social System Theory (Nikias Luhmann). Test reliability was done by Cronbach's Alpha formula, SPSS 24, and Pearson's Correlation Test,